Associations between Thai children’s exposure to unhealthy food marketing and their diet-related outcomes: findings from a national cross-sectional survey - Nongnuch Jindarattanaporn; Bridget Kelly; Salakjit Chuenchom (International Journal of Adolescence and Youth)
The objective of this study was to examine associations between children’s exposure to food marketing and their liking, purchase and consumption of unhealthy foods in Thailand. A face-to-face cross-sectional survey was conducted with a nationally representative sample of 4,117 Thai children aged 6–18 years. Ordinal logistic regression models were applied to determine the association between marketing exposures and liking, purchase and consumption of unhealthy foods. Of all children, 78.8% reported seeing cartoons on food packaging in the past week, while 72.5% had seen a celebrity or online influencer endorses a product. Most children (84%) reported being exposed to marketing for unhealthy foods through social media in the past week. Exposure to unhealthy food marketing was positively associated with children’s preferences for, and purchases and intakes of, unhealthy foods. Comprehensive regulations are required in Thailand to limit children’s exposure to, and the persuasive power of, unhealthy food marketing.